(3CeGdi GHf GdeWjYs
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3dG hdjG Gddg ef Cgd OGQ GdNdhO MOKfG CHh GdaVd eMeO Hf YeQ Hf CMeO GdGOjH GdchcHi bGd cGf QShd Gddg Udi Gddg Ydjg hSde jbhd Gddge GLYdfi GcKQ TcQc hGYXe PcQc hGMaX hUjJc hGbHd fUjMJc s
(3BNQgG (B:s
(3abGd YbHI Hf YGeQ QVi Gddg Yfg gcPG SeYJg ef ai QShd Gddg Udi Gddg Ydjg hSde s
(3HBNQgG bQGAI SfI (B647 (3g` hYdjgG NW EHQGgje Hf YHO GdQMje Hf LeGYI hai CUdgG Gdefbhd efg SeGY SfI (B566 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs